Identification and characterization of polymorphic microsatellite loci in the blue shark Prionace glauca, and cross-amplification in other shark species - Mendonca, F. F. [UNESP]; Ussami, L. H. F. [UNESP]; Hashimoto, D. T. [UNESP]; Pereira, L. H. G. [UNESP]; Porto-Foresti, Fábio [UNESP]; Oliveira, C. [UNESP]; Gadig, Otto Bismarck Fazzano [UNESP]; Foresti, Fausto [UNESP] (Wiley-Blackwell, 2012)
Two to 14 alleles were found to be segregating per locus (mean 5.2), with observed and expected heterozygosities ranging from 0.08 to 0.78 and 0.08 to 0.94, respectively. Cross-amplification of six of these microsatellite loci indicated that they are also polymorphic in three species of Carcharhiniformes and two species of Lamniformes. The newly developed primers reported here constitute a useful tool for genetic population analyses on Prionace glauca and, potentially, other related species.
Keywords: conservation; elasmobranch; genetic variation; marine ecology; polymorphism; population structure